Comprehension to 14 - Barton, Geoff (Oxford Oxford University Press, 2012)
Trusted in classrooms for over fifteen years, this series of much-loved books has been completely updated to support the latest Key Stage 3 requirements. Bestselling author Geoff Barton has rewritten Comprehension to 14 to retain the same engaging, skills-based approach, but with fresh texts and a variety of engaging activities.
Includes Illustrations
Keywords: Reading Comprehension -- Reading Comprehension--Study and Teaching